Persepsi Guru dan Siswa dalam Pemanfaatan Daur Ulang Sampah sebagai Media Pembelajaran di SMP 5 Anggeraja - Nurhelmi Prayunda; Sitti Asmah; Sri Wahyuni (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The recycling process to be used as a learning medium is one of the efforts in waste processing. The aim of this research is to find out the types of learning media that can be made from waste or used goods and to find out the perceptions of teachers and students of SMP 5 Anggeraja, Enrekang Regency regarding the use of recycled waste as a learning media. This research was carried out at SMP 5 Anggeraja, Enrekang Regency using descriptive qualitative research using the interview method as a research instrument. The subjects in this research were 15 teachers and students of SMP 5 Anggeraja, Enrekang Regency, with 1 science subject teacher and 14 class IX students. Overall, functional learning media from used goods that can be used in science learning activities in schools are Chromosome, DNA and Enzyme media.